Fatal Case of Crimean-Congo Hemorrhagic Fever, Portugal, 2024 - Zé-Zé, Líbia (2024)
We report a fatal case of Crimean-Congo hemorrhagic fever in Portugal. An 83-year-old man, initially suspected of having Mediterranean spotted fever, was later confirmed to have Crimean-Congo hemorrhagic fever by the detection of viral genome in the patient's serum and the presence of specific IgM antibodies.